Understanding the Pesticide Label for Citrus Grove Workers - Brian Boman; Darren Cole; Steve Futch; Ward Gunter; Jack W. Hebb; P. Chris Wilson (EDIS, 2009)
Revised! ABE-367, a 5-page fact sheet by Brian Boman, Darren Cole, Steve Futch, Ward Gunter, Jack Hebb, and Chris Wilson, is part of the Best Management Practices (BMPs) for Citrus Grove Workers series. It emphasizes the importance of reading pesticide labels, the risks of misusing pesticides, and what is on the label. Includes a 10-question quiz and references. Published by the UF Department of Agricultural and Biological Engineering, March 2009.